INFLUENCE OF GINKGO BILOBA ON BIRTH WEIGHT AND HISTOMORPHOMETRIC CHARACTERISTICS OF NEONATAL KIDNEYS IN ALBINO RATS - A. Salman; A. S. Qureshi; J. A. Khan; R. U. Shahid; F. Deeba; F. Azam (Journal of Animal and Plant Sciences, 2019)
To elucidate the effects of Ginkgo biloba extract during pregnancy on the fetal growth in terms of weight and renal histogenesis, 28 pregnant albino rats (Wistar) were divided into four groups A, B, C and D (n=7). Ginkgo biloba was administered orally @ 3.5, 7 and 14 mg/kg/day to group A, B and C, respectively, from 8th to 20th day of gestation. Group D served as normal group. The animals were weekly weighed and observed for toxicity during pregnancy. After parturition, different morphological features of neonates were measured and euthanized to collect kidneys for length, width, weight, cortical and medullary thickness measurement. Renal sections were prepared by paraffin tissue technique followed by hematoxylin and eosin staining for histological examination. The weight gain was non-significant in dams although significant (P≤0.01) weight reduction was witnessed in neonate’s weight. kidneys weight showed highly significant (P≤0.01) increase in treated groups than controls in dose-dependent manner. Interstitial edema, inflammation, tubular degenerations and hemorrhages were observed in renal sections. This experimental data suggested that extensive use of Ginkgo biloba during second and third trimester of pregnancy has a negative effect on renal genesis, thus, proving its safety to mothers during pregnancy but deleterious effects on renal histogenesis.
Keywords: Ginkgo biloba; birth weight; renal genesis; histogenesis; herbal medicine; reproductive toxicity